In praise of kings : Rajputs, sultans and poets in fifteenth century Gujarat - Kapadia, Aparna (New York Cambridge University Press, 2020)
"Attempts close readings of several narratives that have rarely been used for historical analysis and studies the complex processes that contributed to the formation of Gujarat in the fifteenth century, and how it has subsequently shaped Gujarat's future"
Includes bibliographical references (pages 165-175) and index.
Keywords: Sultans; India--Gujarat